2005
DOI: 10.1586/17434440.2.4.429
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial biology of in-stent restenosis

Abstract: Percutaneous angioplasty is a nonsurgical method able to restore patency in atherosclerotic blood vessels through the expansion of a balloon. The clinical outcome of this technique has been significantly enhanced by the combined deployment of a stent. Although stents are successful in the majority of cases, a large percentage of patients (20-30%) still suffer a second vessel lumen reduction known as in-stent restenosis. In-stent restenosis is recognized to be caused by the mechanical and foreign body challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 97 publications
1
16
0
Order By: Relevance
“…In the case of the implantation of bare metal stents (e.g. stainless steel devices), ISR occurs in 20-30% of cases and its incidence can only be significantly reduced by the use of drug-eluting stents (DESs) [1]. However, the use of these medicated devices has been linked to the occurrence of late thrombosis and patient death by infarction [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the implantation of bare metal stents (e.g. stainless steel devices), ISR occurs in 20-30% of cases and its incidence can only be significantly reduced by the use of drug-eluting stents (DESs) [1]. However, the use of these medicated devices has been linked to the occurrence of late thrombosis and patient death by infarction [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…These are widely recognized to be relevant to ISR owing to their ability to stimulate SMC proliferation [8][9][10]. It has been suggested that the combined surface activation of both inflammatory cells and SMCs play a major role in the thickening of the neointima [1,2,4].…”
Section: Introductionmentioning
confidence: 99%
“…1 However, clinical studies have shown that over 20% of the patients still undergo restenosis after stent deployment unless drug-eluting stents are implanted. 1 Recent investigations suggest that instent restenosis (ISR) is a consequence of the tissue damage following balloon and stent expansion.…”
Section: Introductionmentioning
confidence: 99%
“…1 However, clinical studies have shown that over 20% of the patients still undergo restenosis after stent deployment unless drug-eluting stents are implanted. 1 Recent investigations suggest that instent restenosis (ISR) is a consequence of the tissue damage following balloon and stent expansion. 2 In particular, when stent struts penetrate the atherosclerotic plaque, they activate cells of the monocyte/ macrophage (MM) lineage as well as platelets.…”
Section: Introductionmentioning
confidence: 99%
“…ISR remains a significant clinical problem despite advances in stent design and the use of drug-eluting stents [2]. Metal alloys commonly used for stents are subject to stress/strain fracture related to crevice and pitting corrosion due to both mechanical and environmental factors.…”
Section: Introductionmentioning
confidence: 99%